A2Zn3P4S13 (A = Rb and Cs): First Infrared Nonlinear Optical Materials with Mixed Thiophosphate Functional Motifs PS4 and P2S6. Issue 23 (6th June 2022) - Li, Ming-Ze; Jiang, Lin-Tao; Pei, Shao-Min; Liu, Bin-Wen; Jiang, Xiao-Ming; Guo, Guo-Cong
Abstract : Two new IR NLO thiophosphates A2 Zn3 P4 S13 (A = Rb, Cs) feature [Zn3 P4 S13 ] anionic framework and contain two types of NLO-active thiophosphate units (PS4 and P2 S6 ), which to our best knowledge is unprecedented in known IR NLO thiophosphates. Abstract : Two new IR NLO compounds, namely Rb2 Zn3 P4 S13 (1 ) and Cs2 Zn3 P4 S13 (2 ), have been obtained by introducing d 10 closed-shell cations in an alkali-metal containing thiophosphate system. Compounds 1 and 2 are isostructural and feature a 3D [Zn3 P4 S13 ] anionic framework. Both compounds exhibit moderate phase-matching SHG intensities at 1910 nm (0.1 × AGS for 1 and 2 ) and high LIDTs (6.1 × AGS for 1 and 5.2 × AGS for 2 ). They have wide transparent regions of 2.5–17.7 μm and 2.5–17.0 μm for 1 and 2, respectively, which cover the important far-IR atmospheric window of 3–5 and 8–14 μm for practical applications. Both compounds simultaneously contain two types of NLO-active thiophosphate units (PS4 and P2 S6 ) in their structures, which to the best of our knowledge, is unprecedented in known IR NLO thiophosphates. The NLO efficiencies of 1 and 2 are mainly due to the covalent [Zn2 P2 S7 ] 2− framework, in which the contribution of P2 S6 units is remarkably larger than that of the PS4 units. This work sheds light on the design of promising IR NLO materials by mixing different thiophosphate functional motifs.